Answer:
z = (3/√2) + (1/√2)î = (1/√2) [3 + i] = (2.1213 + 0.7071i)
OR
z = -(3/√2) + i(1/√2) = (1/√2) [-3 + i] = (-2.1213 + 0.7071i)
p = (3/√2) = 2.1213
q = (1/√2) = 0.7071
OR
p = (-3/√2) = -2.1213
q = (1/√2) = 0.7071
Step-by-step explanation:
z = √(4 + 3i)
Let the complex number z be equal to
z = p + qi
So, we can write
z = p + qi = √(4 + 3i)
p + qi = √(4 + 3i)
Square both sides
(p + qi)² = [√(4 + 3i)]²
p² + pqi + pqi + (qi)² = (4 + 3i)
p² + 2pqi + q²i² = 4 + 3i
note that i² = -1
p² + 2pqi - q² = 4 + 3i
(p² - q²) + 2pqi = 4 + 3i
Comparing both sides, and them equating the real parts on both sides to each other and the complex parts to each other
(p² - q²) = 4 (eqn 1)
2pq = 3 (eqn 2)
From eqn 2
p = (3/2q)
p² = (9/4q²)
Substituting this into eqn 1
(9/4q²) - q² = 4
multiplying through by 4q²
9 - 4q⁴ = 16q²
4q⁴ + 16q² - 9 = 0
let q² = x, q⁴ = x²
4x² + 16x - 9 = 0
Solving the quadratic equation
x = 0.5 or -4.5
q² = 4
q² = 0.5 or q² = -4.5
q = √0.5 or √-4.5
q = (1/√2) = (√2)/2 = 0.7071
Or q = i(3/√2) = i(3√2)/2 = 2.1213I
p = (3/2q)
If q = (1/√2) = (√2)/2 = 0.7071
p = (3/√2) = (3√2)/2 = 2.1213
if q = i(3/√2) = i(3√2)/2 = 2.1213I
p = i(1/√2) = i(√2)/2 = 0.7071i
z = p + qi
If q = (1/√2) = (√2)/2 = 0.7071
p = (3/√2) = (3√2)/2 = 2.1213
z = (3/√2) + (1/√2)î = (1/√2) [3 + i]
= 2.1213 + 0.7071i
if q = i(3/√2) = i(3√2)/2 = 2.1213I
p = i(1/√2) = i(√2)/2 = 0.7071i
z = i(1/√2) + [i(3/√2) × i]
z = i(1/√2) - (3/√2)
z = -(3/√2) + i(1/√2)
z = (1/√2) [-3 + i]
z = -2.1213 + 0.7071i
Hope this Helps!!!